2010
DOI: 10.1063/1.3459143
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of graphene-like electronic signature in silicene nanoribbons

Abstract: We report on the electronic properties of straight, 1.6 nm wide, silicene nanoribbons on Ag(110), arranged in a one-dimensional grating with a pitch of 2 nm, whose high-resolution scanning tunneling microscopy images reveal a honeycomb geometry. Angle-resolved photoemission shows quantum confined electronic states of one-dimensional character. The silicon band dispersion along the direction of the nanoribbons suggests a behavior analogous to the Dirac cones of graphene on different substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
468
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 597 publications
(481 citation statements)
references
References 16 publications
6
468
0
7
Order By: Relevance
“…The metastable lattice that we find is the same as the "low-buckled" structure found by Cahangirov et al 3 The experimental results for the lattice parameter depend on the choice of substrate on which the silicene is grown. 5,6 The extent to which theoretical results obtained for freestanding silicene are applicable to the silicene samples that have been produced to date is therefore unclear.…”
Section: A Comparison With Theoretical and Experimental Results In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The metastable lattice that we find is the same as the "low-buckled" structure found by Cahangirov et al 3 The experimental results for the lattice parameter depend on the choice of substrate on which the silicene is grown. 5,6 The extent to which theoretical results obtained for freestanding silicene are applicable to the silicene samples that have been produced to date is therefore unclear.…”
Section: A Comparison With Theoretical and Experimental Results In Tmentioning
confidence: 99%
“…1,2 A close relative of graphene, a 2D honeycomb lattice of Si atoms called silicene, 3 does not occur in nature, but nanoribbons of silicene have been synthesized on metal surfaces. [4][5][6] Due to the similarity of the lattice structures, the band structure of silicene resembles that of graphene, featuring Dirac-type electron dispersion in the vicinity of the corners of its hexagonal Brillouin zone (BZ). 7 Moreover, silicene has been shown theoretically to be metastable as a freestanding 2D crystal, 3 implying that it is possible to transfer silicene onto an insulating substrate and gate it electrically.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] Most recently, possibility of various combinations of MX 2 type single-layer transitionmetal oxides and dichalcogenides, stable even in freestanding form, was also predicted. 43 The recent synthesis of silicene, [44][45][46] the silicon analogue of graphene has opened a new avenue to nanoscale material research. Though the nanotube 47 and fullerene 48 forms of silicon were synthesized earlier, monolayer silicon was presumed not to exist in a freestanding form.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 We have shown that their reactivity towards molecular oxygen is substantially less than that of silicon. 11 In addition, angle-resolved photoelectron spectroscopy (ARPES) measurements showed quantum confined electronic states of a onedimensional character 12 with a dispersion along the length of the NRs, in the vicinity of the X-point of the Brillouin zone suggesting a behavior analogous to the Dirac cones of graphene. 12 On the Ag(111) surface, a continuous two dimensional (2D) sheet of silicene presenting a (2√3x2√3) R30° superstructure, has been observed by scanning tunneling microscopy (STM).…”
mentioning
confidence: 99%
“…11 In addition, angle-resolved photoelectron spectroscopy (ARPES) measurements showed quantum confined electronic states of a onedimensional character 12 with a dispersion along the length of the NRs, in the vicinity of the X-point of the Brillouin zone suggesting a behavior analogous to the Dirac cones of graphene. 12 On the Ag(111) surface, a continuous two dimensional (2D) sheet of silicene presenting a (2√3x2√3) R30° superstructure, has been observed by scanning tunneling microscopy (STM). 9 Following our pioneering work, several groups have successfully grown silicene on Ag(111) and reported the existence of different ordered phases 13-16 (2√3x2√3) R30°, (4x4), and (√13x√13) R13.9°.…”
mentioning
confidence: 99%